ENHANCING EFL STUDENT ENGAGEMENT THROUGH DEEP LEARNING APPROACHES - Aditama, Madya; Suwarna; Djoko Prannowo, Dwiyanto; Ainun Najib, Muhammad Reza; R Iswari, Ismi Islamia (Melekliterasi Press, 2025)
This study explores the influence of deep learning strategies on student engagement in EFL classrooms and examines teachers’ perceptions of their implementation. Conducted at SMP N 2 Bandar, the research employed a qualitative phenomenological approach involving classroom observations, semi-structured interviews, and documentation. The findings reveal that strategies such as problem-based learning, collaborative tasks, reflective questioning, and scaffolded critical thinking significantly enhance cognitive, emotional, and behavioral engagement among students. Observable indicators included increased participation, group collaboration, on-task behavior, and curiosity-driven questioning. Teachers reported that these approaches encouraged more meaningful learning, boosted student confidence, and fostered greater ownership of the learning process. Despite facing challenges like limited time and diverse student readiness, teachers believed that deep learning fostered a more dynamic and student-centered environment. The study concludes that deep learning strategies, when applied consistently, can transform EFL instruction by making learning more interactive, relevant, and engaging. These findings offer practical implications for English teachers seeking to promote deeper involvement and long-term motivation in language learning.